Radiological and histopathological evaluation of experimentally-induced periapical lesion in rats - Renata Cordeiro Teixeira; Cassia Maria Fischer Rubira; Gerson Francisco Assis; José Roberto Pereira Lauris; Tania Mary Cestari; Izabel Regina Fischer Rubira-Bullen (University of São Paulo, 2011)
OBJECTIVE: This study evaluated experimentally-induced periapical bone loss sites using digital radiographic and histopathologic parameters. MATERIAL AND METHODS: Twenty-seven Wistar rats were submitted to coronal opening of their mandibular right first molars. They were radiographed at 2, 15 and 30 days after the operative procedure by two digital radiographic storage phosphor plates (Digora®). The images were analyzed by creating a region of interest at the periapical region of each tooth (ImageJ) and registering the corresponding pixel values. After the sacrifice, the specimens were submitted to microscopic analysis in order to confirm the pulpal and periapical status of the tooth. RESULTS: There was significant statistically difference between the control and test sides in all the experimental periods regarding the pixel values (two-way ANOVA; p<0.05). CONCLUSIONS: The microscopic analysis proved that a periapical disease development occurred during the experimental periods with an evolution from pulpal necrosis to periapical bone resorption.